General practitioners' perceptions of irritable bowel syndrome: a Q-methodological study. (14th July 2017) - Bradley, Stephen; Alderson, Sarah; Ford, Alexander C; Foy, Robbie
Abstract: Background: Irritable bowel syndrome (IBS) is a common disorder that imposes a significant burden upon societies, health care and quality of life, worldwide. While a diverse range of patient viewpoints on IBS have been explored, the opinions of the GPs they ideally need to develop therapeutic partnerships with are less well defined. Objective: To explore how GPs perceive IBS, using Q-methodology, which allows quantitative interpretation of qualitative data. Design and Setting: A Q-methodological study of GPs in Leeds, UK. Method: Thirty-three GPs completed an online Q-sort in which they ranked their level of agreement with 66 statements. Factor analysis of the Q-sorts was performed to determine the accounts that predominated in understandings of IBS. Ten of the GPs were interviewed in person and responses to the statements recorded to help explain the accounts. Results: Analysis yielded one predominant account shared by all GPs—that IBS was a largely psychological disorder. This account overshadowed a debate represented by a minority, polarized between those who viewed IBS as almost exclusively psychological, versus those who believed IBS had an organic basis, with a psychological component. The overwhelming similarity in responses indicates that all GPs shared a common perspective on IBS. Interviews suggested degrees of uncertainty and discomfort around the aetiology of IBS. Conclusion: There was overwhelming agreement in the way GPs perceived IBS. This contrasts with the range of patient accounts of IBS and may explain why both GPs and their patients face difficult negotiations in achieving therapeutic relationships.